Dynamics Of Legal Aid Provision In The Indonesian Criminal Justice System: A Comparative Study Of The Netherlands, Australia, And South Africa - Nuraharja Adi Partha, Putu Gde; Lia Puspita, Putu; Setyawan, Fendi (Dinasti Research, 2024)
The Dynamics of Legal Aid Provision within the Legal System Aimed at Providing Limited Access to Justice and Referring to Core Principles Including Presumption of Innocence, Right to Know the Nature of Charges Against the Defendant, and Ability to Effectively Defend Against Those Charges in a Fair and Open Trial by an Independent and Impartial Court. The legal research method used in this study is normative juridical research that refers to the legal basis related to legal norms applicable in a country. This research approach uses legislative and comparative approaches regarding legal aid provision in Australia, the Netherlands, and South Africa. The research findings indicate that legal aid provided by lawyers representing their clients to provide legal assistance is at the core of the right to fair trial and must be provided to anyone as a concrete manifestation of the principle of equality before the law. Therefore, access to justice is not only for those with high social status but also for lower- and middle-class individuals who have economic limitations and have the same right to be treated fairly under the law. Based on these aspects, this paper will comprehensively discuss legal aid provision in the criminal justice system in the Netherlands, Australia, and South Africa.